In situ production of active vitamin B12 in cereal matrices using Propionibacterium freudenreichii. Issue 1 (12th November 2017) - Chamlagain, Bhawani; Sugito, Tessa A.; Deptula, Paulina; Edelmann, Minnamari; Kariluoto, Susanna; Varmanen, Pekka; Piironen, Vieno
Abstract: The in situ production of active vitamin B12 was investigated in aqueous cereal‐based matrices with three strains of food‐grade Propionibacterium freudenreichii . Matrices prepared from malted barley flour (33% w/v; BM), barley flour (6%; BF), and wheat aleurone (15%; AM) were fermented. The effect of cobalt and the lower ligand 5, 6‐dimethylbenzimidazole (DMBI) or its natural precursors (riboflavin and nicotinamide) on active B12 production was evaluated. Active B12 production was confirmed by UHPLC–UV–MS analysis. A B12 content of 12–37 μg·kg −1 was produced in BM; this content increased 10‐fold with cobalt and reached 940–1, 480 μg·kg −1 with both cobalt and DMBI. With riboflavin and nicotinamide, B12 production in cobalt‐supplemented BM increased to 712 μg·kg −1 . Approximately, 10 μg·kg −1 was achieved in BF and AM and was increased to 80 μg·kg −1 in BF and 260 μg·kg −1 in AM with cobalt and DMBI. The UHPLC and microbiological assay (MBA) results agreed when both cobalt and DMBI or riboflavin and nicotinamide were supplemented. However, MBA gave ca. 20%–40% higher results in BM and AM supplemented with cobalt, indicating the presence of human inactive analogues, such as pseudovitamin B12. This study demonstrates that cereal products can be naturally fortified with active B12 to a nutritionally relevant level by fermenting with P. freudenreichii . Abstract : This study demonstrates that plant‐based foods can naturally be fortified with active vitamin B12 at a nutritionally relevant level by fermentation, using food‐grade microorganisms.